APLIKASI PENGAJUAN ANGGARAN DENGAN MENGGUNAKAN METODE PROTOTYPE - Taqa, Dara; Mhd Raja Doly Bahari; Armansyah (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2023)
The urgency of digital transformation is growing for companies, including government institutions. Budget submissions in large companies, including government agencies such as the Financial and Asset Management Agency of Medan City, need to undergo transformation for the purpose of effectiveness and efficiency. In practice, budget submissions in this department are still conventional, hence budget realization often occurs untimely. This research aims to develop a budget submission application that can help minimize delays in budget submission and realization. The development of this application uses the System Development Life Cycle (SDLC) approach and the prototype method to ensure that the developed application meets user needs. Evaluation conducted with prospective application users in the institution assesses that the application is relevant to their needs, while application testing using the black-box method indicates positive results.